1999
DOI: 10.1021/ja9817139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the North 1 Unit of the Cephalostatin Family from Hecogenin Acetate1

Abstract: Hecogenin acetate (1) was converted to North 1 azidoketone 5 involving several key transformations:  (1) conversion of cyclic sulfate 33b to allylic alcohol 40 via Reich iodoso olefination; (2) E-ring annulation via intermolecular oxygen alkylation of highly functionalized secondary alcohol 40 using rhodium-catalyzed decomposition of an α-diazophosphonoacetate to provide α-alkoxyphosphonoacetate 52, with subsequent intramolecular Wadsworth−Emmons reaction to provide alkoxydihydrofuran 53; and (3) establishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 102 publications
1
34
0
Order By: Relevance
“…The synthetic pathway started with the transformation of a spiroketal functionality of tigogenin to a keto ester using the method previously described by Micovic et al, and modified by Fushs et al [67]. …”
Section: Polyoxygenated Steroids and Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic pathway started with the transformation of a spiroketal functionality of tigogenin to a keto ester using the method previously described by Micovic et al, and modified by Fushs et al [67]. …”
Section: Polyoxygenated Steroids and Derivativesmentioning
confidence: 99%
“…The synthetic pathway started with the transformation of a spiroketal functionality of tigogenin to a keto ester using the method previously described by Micovic et al, and modified by Fushs et al [67]. The keto ester I was then transformed to a trihydroxyl intermediate II by Grignard reagent which, after oxidation, gave compounds 21 and 22.…”
Section: Polyoxygenated Steroids and Derivativesmentioning
confidence: 99%
“…Meanwhile, Fuchs and co-workers reported the first total synthesis of 1 and other cephalostatin members [6][7][8]. Very recently, Shair et al have reported the second total synthesis of 1 using an elegant allylic oxidation method of C-18 [9].…”
mentioning
confidence: 99%
“…The North 1 synthesis44 began with the reduction of hecogenin acetate 32 with DIBAL-H followed by acylation to provide rockogenin diacetate (Scheme 22). Rockogenin diacetate was converted into pseudorockogenin triacetate 69 by pyridinium hydrochloride catalyzed reaction with acetic anhydride.…”
Section: Classical First Generation Synthesesmentioning
confidence: 99%